Pengaruh Kepemimpinan Transformasional Kepala Sekolah Terhadap Kinerja Guru - Sari, Nurul (Journal of Innovation in Teaching and Instructional Media, 2025)
This study aims to examine the extent to which the principal's transformational leadership influences teachers’ performance at SD Negeri 62 Palembang. This study employs a quantitative approach with an ex post facto research design. The research population consists of all teachers at SD Negeri 62 Palembang, while the sample is selected using a saturated sampling technique. Data collection was conducted through a questionnaire that had been tested for validity and reliability. The independent variable in this study is the principal’s transformational leadership, measured based on dimensions such as inspiration and motivation, intellectual stimulation, and individualized consideration. Meanwhile, the dependent variable is teacher performance, which includes aspects of professionalism, creativity, and job satisfaction. Data analysis was conducted using a simple regression test to examine the direct influence between the independent and dependent variables. The research findings indicate a significant influence of the principal's transformational leadership on teacher performance. The dimensions of inspiration and motivation, as well as intellectual stimulation, contributed the most to improving teacher performance. This indicates that a principal who can inspire the school's vision, motivate teachers to achieve common goals, and encourage the continuous development of teacher competencies will positively impact teacher performance. These findings align with previous studies that highlight the importance of transformational leadership in improving organizational performance. Effective transformational leadership can create a positive school climate, encourage teachers to continuously learn and grow, and enhance their sense of belonging and commitment to the school.